Photocatalytic degradation of methylene blue and tetracycline under visible light by fabricated carbon quantum dot decorated TiO2 nanotubes - Jyoti Rawat; Charu Dwivedi; Pankaj Sharma (Nanocomposites)
This work presents the synthesis of CQD decorated TiO2 nanotubes (CQDs/TNTs) from CQD-decorated TiO2 (CQDs/TiO2) using the hydrothermal method. UV-Vis diffuse reflectance spectroscopy (UV-DRS) reveals that TiO2 nanoparticles (NPs) have a band gap of 3.02 eV, while CQDs/TNTs exhibit a band gap of 2.89 eV. Brunauer-Emmett-Teller (BET) analysis shows that the CQDs/TNTs composite exhibits an increased surface area, average pore diameter, and a greater number of active sites, thus enhancing its photocatalytic efficiency. The Fourier transform infrared spectroscopy (FTIR) results are consistent with the X-ray spectroscopy (XPS), and the Raman studies confirm that the CQDs are decorated on TiO2 TNTs, significantly improving the crystallinity. X-ray diffraction (XRD) results suggest that the decoration of CQDs onto TiO2 TNTs significantly hinders crystalline growth. The composites show excellent photocatalytic activity against methylene blue (MB) and tetracycline (TC) as model pollutants. Kinetic analysis indicates that the photodegradation follows pseudo-second-order kinetics.